2005
DOI: 10.30843/nzpp.2005.58.4282
|View full text |Cite
|
Sign up to set email alerts
|

Soil biota associated with endophyteinfected tall fescue in the field

Abstract: Invertebrates present in soil samples taken from plots of tall fescue (Festuca arundinacea) infected with two nontoxic strains of Neotyphodium endophyte (AR501 and AR542) at Aorangi near Palmerston North and one strain (AR501) at Lincoln in Canterbury together with endophytefree controls at both sites were determined in autumn 2002 Roots taken from these samples were stained and checked for the presence of arbuscular mycorrhiza At Lincoln numbers of root aphid (Aploneura lentisci) associated with plants infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…It is therefore likely to be an important pest in drought-prone areas where tall fescue would be used. Popay & Jensen (2005) found more root aphid under endophyte-free (Nil) than AR542 and AR501 field plots in a trial at Aorangi, New Zealand, but differences were not statistically significant. This paper describes experiments to further assess the efficacy of several non-toxic novel endophyte strains on root aphid and to investigate whether the effect is due to deterrence or toxicity.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is therefore likely to be an important pest in drought-prone areas where tall fescue would be used. Popay & Jensen (2005) found more root aphid under endophyte-free (Nil) than AR542 and AR501 field plots in a trial at Aorangi, New Zealand, but differences were not statistically significant. This paper describes experiments to further assess the efficacy of several non-toxic novel endophyte strains on root aphid and to investigate whether the effect is due to deterrence or toxicity.…”
Section: Introductionmentioning
confidence: 81%
“…Root aphid, Aploneura lentisci, is common in pasture throughout New Zealand and has been shown in pot trials to reduce growth of ryegrass when plants are under stress (Popay & Jensen 2005). It is therefore likely to be an important pest in drought-prone areas where tall fescue would be used.…”
Section: Introductionmentioning
confidence: 99%
“…Adult scarabs, too, attract birds associated with strike hazard (Buckley and McCarthy, 1994;Bernhardt et al, 2010;Washburn et al, 2011). Endophytes tend to have weak or no effects on abundance of grubs, earthworms, or other soil biota (Potter et al, 1992;Davidson and Potter, 1995;Koppenhöfer et al, 2003;Popay and Jensen, 2005;Lemons et al, 2005;Rudgers and Clay, 2007;Keathley and Potter, 2012), which is expected given their localization in aboveground tissues. Endophytic alkaloids appear to become attenuated up through the food web and to have little or no effect on field abundance of predatory insects and spiders (Davidson and Potter, 1995;Rudgers and Clay, 2007;Keathley and Potter, 2012;this study).…”
Section: Discussion and Applicationsmentioning
confidence: 98%
“…Previous studies demonstrated that EP infection can suppress mycorrhizal colonisation of grass roots in tall fescue (Chu-Chou et al 1992;Guo et al 1992), perennial ryegrass (Müller 2003) and annual ryegrass (Omacini et al 2006). However, Popay and Jensen (2005) reported that under field conditions neither the proportion of root segments infected with AM nor the level of root infection differed between EP-infected and EP-free treatments. Furthermore, Novas et al (2005) found that roots of EP-infected Bromus setifolius populations were colonised more extensively by AM fungi than those of EP-free populations.…”
Section: Introductionmentioning
confidence: 96%